Turkish Neonatal Society guideline on nutrition of the healthy term newborn - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2018)
Research shows strong evidence that breastfeeding offers many health benefits for infants and mothers, as well as potential economic and environmental benefits for communities. The World Health Organization recommends breastfeeding exclusively for up to 6 months of age, with continued breastfeeding along with appropriate complementary foods up to two years of age or beyond.
Keywords: Breast milk; breastfeeding; lactation; term baby; COLD-STORAGE; ENERGY